Spatial dynamic patterns of saltmarsh vegetation in southern Hangzhou Bay: Exotic and native species - Si-long Huang; Yi-ning Chen; Yan Li (Water Science and Engineering, 2020)
A saltmarsh has developed rapidly on the mudflat of Andong Shoal, in southern Hangzhou Bay, over the last decade since embankment. The saltmarsh vegetation changes are driven by both sediment dynamic conditions and the competition between the exotic species Spartina alterniflora (S. alterniflora) and the native species Scirpus mariqueter (S. mariqueter). This study attempted to investigate large-scale spatial variations in the exotic and native species, by analyzing and interpreting a time series (2016–2018) of high-resolution (less than 1 m) remote sensing images. The total area of the saltmarsh increased at a rate of 1.07 km2/year, due to the accretion of the whole tidal flat. The spatial patterns revealed a new bimodal pattern for S. alterniflora invasion. S. alterniflora expanded over the upper to middle saltmarsh at a rate of 1.68 km2/year. However, the S. alterniflora patches at the seaward edge expanded at a negative rate of −0.005 km2/year, indicating a different pattern in competition: S. alterniflora had more advantages in the upper saltmarsh, while S. mariqueter had more advantages in the pioneer zone with low elevation. Consequently, S. alterniflora mainly established new habitats by invading S. mariqueter in the middle saltmarsh, but S. mariqueter occupied the bare mudflat for tradeoff. Our results aindicated that the interspecific competition result between S. alterniflora and S. mariqueter depended on elevation, and low elevation might create a favorable environment for S. mariqueter to win the competition with exotic species. This finding could be applied to future invasive species control and saltmarsh management.